Organization of early assistance to children with autism spectrum disorders:a review of domestic and foreign experience (Gumilyov Journal of Pedagogy, 2025)
This scientific article is devoted to the organization of the early care system for children with ASD in the Republic of Kazakhstan, taking into account domestic and foreign experience. The relevance of the study is due to the growing prevalence of autism worldwide, including in Kazakhstan, where there is an annual increase in the number of children with this diagnosis.The following methods were used in the research: comparative pedagogical analysis, study of normative documents on the research problem, generalization of existing experience on the research problem, pedagogical experiment.The article presents modern approaches to the organization of early care for children with ASD. Effective methods of corrective action are considered, including ABA therapy, sensory integration, Early Start Denver Model, EarlyBird, DIR/Floortime.Special attention in the study is paid to the application of approaches in the natural environment of the child. The inclusion of a child in a familiar environment contributes to the optimal development of new skills and their application in real-life situations. The above empirical research results also show that the involvement of parents in the process of correction and development of a child in a natural environment significantly improves the social, communicative and behavioral skills of children with ASD, as well as improves the interaction and emotional involvement of parents.